Evaluating Inpatient Asthma Management Practices in Florida Hospitals - Alexandra C.H. Nowakowski; Henry J. Carretta; Julie K. Dudley; Jamie R. Forrest; Abbey N. Folsom (University of North Florida, 2015)
We evaluated inpatient asthma management practices in 10 Florida hospitals. We wanted to learn about care protocols, instrumental resources, and use of evidence-based guidelines. We sought to recommend strategies for improving care based on gaps identified by this study. We developed a survey that included detailed questions on care strategies and resources. Guidelines from the National Heart, Lung, and Blood Institute (NHLBI) in the Expert Panel Report 3 (EPR-3) for the Diagnosis and Management of Asthma were a primary focus. Hospitals were given the option of completing their surveys by phone or email. Data were analyzed via content coding of completed surveys. Most participating hospitals had robust protocols and resources in place for inpatient asthma management, and continually reassessed these resources for quality improvement. Overall, inpatient care practices at these hospitals adhered strongly to national guidelines for asthma management. Inpatient asthma care practices at surveyed Florida hospitals are largely robust, evidence-based, and constantly improving. Our findings suggest not only that hospitals in Florida are deeply committed to effective asthma management, but also that they have active interest in collaborating with one another to further improve care.